Evolving Technology on Muslim Family: Conflicts and Solutions - Muhd Adnan, Nurul Izwah; Muhd Adnan, Hafizuddin; Muhd Adnan, Nurul Ilyana (El-Usrah: Jurnal Hukum Keluarga, 2025)
Nowadays, information and communication technology (ICT) is being used in completing daily tasks of Muslims family. The tasks are including education, management services, banking, and more. The rapid developing of the technology such as gadgets, online services affected the families that lead to dilemma for society. There are positive and negative impacts of the ICT. Even though there are advantages, there are also conflicts and shortcomings that affected our religious beliefs and ethics. Therefore, this paper will discuss this issue and suggest solutions from the Islamic perspective and alternative solutions. As a result, this paper suggests that Muslims should utilize ICT wisely, intelligently and with integrity, guided by Shariah.